2012
DOI: 10.1111/epi.12031
|View full text |Cite
|
Sign up to set email alerts
|

The emerging role of DNA methylation in epileptogenesis

Abstract: SUMMARYDNA methylation is a covalent chromatin modification, characterized by the biochemical addition of a methyl group (-CH3) to cytosine nucleotides via a DNA methyltransferase enzyme. 5¢-Methylcytosine (5-mC), frequently called the fifth base, has been implicated in genome stability, silencing of transposable elements, and repression of gene expression. Through the latter, DNA methylation dynamics broadly influence brain development, function, and aging. Aberrant DNA methylation patterns, either localized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(67 citation statements)
references
References 105 publications
(121 reference statements)
5
62
0
Order By: Relevance
“…This finding is in line with an animal model meta-analysis conducted by Montgomery et al, confirming a memoryenhancing effect of SAM [11]. Involvement of SAM in the transmethylation reaction plays a role in the induction of activitydependent synaptic plasticity and memory formation [9,10]. Also, the antioxidant property of SAM could potentially ameliorate the cognitive impairment produced as a result of oxidative stress in the PTZ-induced kindling model [13].…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…This finding is in line with an animal model meta-analysis conducted by Montgomery et al, confirming a memoryenhancing effect of SAM [11]. Involvement of SAM in the transmethylation reaction plays a role in the induction of activitydependent synaptic plasticity and memory formation [9,10]. Also, the antioxidant property of SAM could potentially ameliorate the cognitive impairment produced as a result of oxidative stress in the PTZ-induced kindling model [13].…”
Section: Discussionsupporting
confidence: 81%
“…The novel 'Methylation hypothesis in epilepsy' has hypothesized that a defective transmethylation reaction results in increased seizure susceptibility and cognitive deficit as seen with temporal lobe epilepsy [9]. Involvement of SAM in the transmethylation reaction may contribute to its antiepileptic effect [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CPA6 is involved in the selective biosynthesis of neuroendocrine peptides, and loss-of-function mutations have been related to seizures and epilepsy (Sapio et al 2012). Furthermore, increased DNMT1 and DNMT3A expression have been described in temporal neocortex samples obtained from TLE patients, which is in line with the localized DNA methylation changes described above, but could also point to even broader changes of DNA methylation in the pathogenesis of focal epilepsies (Kobow and Blumcke 2012;Zhu et al 2012). In fact, methyl-CpG-capture-associated massive parallel sequencing (methyl-seq) as well as array-based analyses of genomic DNA methylation patterns in two different rodent seizure models identified genome-wide changes in DNA methylation following status epilepticus (SE) as well as epileptic tolerance (MillerDelaney et al 2012), and identified a methylation signature distinguishing chronic epileptic animals from healthy controls (Kobow et al 2013).…”
Section: Dna Methylation and Epilepsysupporting
confidence: 79%
“…These are emerging pharmacological targets in epilepsy and other neurological disorders, particularly since two drugs (Vidaza and Dacogen) that target all DNA methyltransferases and inhibit DNA methylation are already clinically approved. 20 Interestingly, one of the oldest AEDs, sodium valproate, is also an inhibitor of one of these (histone deacetylase), which when inhibited leads to uncoiling of DNA from histones and therefore generally enhances transcription. Hence valproate may act not only as a regulator of neuronal ion channels but also as a master key regulating transcription of proteins that contribute to a number of chemical and structural changes, including neurogenesis, that occur during epileptogenesis.…”
Section: Epigeneticsmentioning
confidence: 99%